Icariin alleviates osteoarthritis by regulating autophagy of chondrocytes by mediating PI3K/AKT/mTOR signaling. Issue 1 (1st January 2021) - Tang, Yanghua; Li, Yongfu; Xin, Dawei; Chen, Lin; Xiong, Zhenfei; Yu, Xuezi
ABSTRACT: Osteoarthritis (OA) is a chronic degenerative disease that significantly impacts the quality of life of the elderly population. Recently, the pathogenesis of OA has been reported to involve autophagy in chondrocytes. Intriguingly, icariin, one of the main components of epimedium, exerts multiple pharmacological effects, including a protective effect against chondrocyte damage. Thus, we aimed to investigate the therapeutic effect of icariin on OA and its potential underlying mechanism by using a rat model of OA. After treatment with icariin or an autophagy activator (rapamycin) or inhibitor (3-methyladenine), OA chondrocyte viability was measured using the CCK-8 assay, apoptosis in the chondrocytes was evaluated using the acridine orange-propidium iodide assay and flow cytometry, and OA tissue pathological state was assessed using micro-CT scanning and safranin O staining. Furthermore, immunohistochemical staining was used to measure the expression level of Beclin-1 and immunofluorescence labeling was used to visualize LC3 expression, and western blotting was used to determine the expression levels of autophagy proteins and key proteins in the PI3K signaling pathway. The apoptotic rate of OA chondrocytes was markedly elevated by 3-methyladenine and suppressed by rapamycin and icariin; autophagy genes were drastically downregulated in the 3-methyladenine group and upregulated in the rapamycin and icariin groups; and the PI3K/AKT/mTOR signaling pathway was activated by 3-methyladenine and inhibited by rapamycin and icariin. Notably, following treatment with rapamycin and icariin, the severe pathological state in OA cartilage tissues was substantially alleviated, and this was accompanied by activated autophagy and inhibited PI3K signaling in the cartilage tissues. Taken together, these findings indicate that icariin alleviates OA by regulating the autophagy of chondrocytes by mediating PI3K/AKT/mTOR signaling. Graphical abstract: uf0001